Lithium ion battery electrolyte, preparation method thereof, and lithium ion battery

By adding tri-thiophene boric acid to the lithium-ion battery electrolyte to form a stable interface mask, the problem of electrolyte decomposition of LNMO positive electrode material at high potential is solved, and the safety performance and cycle life of the battery are improved.

CN118198496BActive Publication Date: 2025-03-25HUBEI ENERGY GRP NEW ENERGY DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410431302.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2025-03-25
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

When the LNMO cathode material of lithium-ion batteries works under a high potential platform, the electrolyte is easily decomposed, resulting in a decrease in battery safety performance and cycle life.

Method used

Tri-thiophene boric acid (3-TPBA) is used as an additive to form a controllable, high-stability, low-impedance interface mask, inhibit the decomposition of the electrolyte and improve the conduction speed of lithium ions.

Benefits of technology

It significantly improves the safety performance and cycle life of lithium-ion batteries, can adapt to cut-off voltages up to 4.9V, and improves the rate performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118198496B_ABST
    Figure CN118198496B_ABST
Patent Text Reader

Abstract

The present invention provides a lithium ion battery electrolyte, including: an electrolyte lithium salt, an organic solvent and an additive; wherein the additive is tri-thiophene boronic acid (3-TPBA). As an additive, 3-TPBA has excellent film-forming ability on the surface of the positive electrode material, can be oxidized before the electrolyte components, and the interface formed by its induction can effectively suppress the continuous decomposition of the electrolyte and ensure the stability and integrity of the electrode structure; on the other hand, 3-TPBA can also be reduced in advance to form a SEI interface film at the graphite negative electrode, and effectively reduce the membrane impedance and interface impedance, and improve the cycle stability of the graphite negative electrode at a high rate. The electrolyte prepared by the present invention can adapt to the high potential platform of the LNMO positive electrode material in the lithium ion battery, suppress the decomposition of the electrolyte by forming a controllable, highly stable, low-impedance interface film, and significantly improve the safety performance and cycle life of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium ion battery electrolyte and a preparation method thereof, and also relates to a lithium ion battery. Background Art

[0002] In order to solve the serious challenges of non-renewable (fossil) resources and their combustion, such as environmental pollution and global warming, the main strategy proposed is to integrate clean and efficient energy storage technologies based on renewable energy (such as wind energy, solar energy, etc.) into different energy fields, especially in transportation and energy storage. At present, rechargeable battery technology is the most feasible concept for these applications. Lithium-ion batteries are the most advanced rechargeable battery technology at present. They not only dominate the small-scale portable electronic product market, but also have been considered as the technology of choice in the field of electric drive vehicles and electrochemical energy storage.

[0003] Spinel LiNi 0.5 Mn 1.5 O4 (LNMO) material is derived from Ni doping of LiMn2O4. It has low cost (cheap raw materials and simple synthesis conditions), 3D lithium ion migration channel (high Li + migration rate), 147.6 mAh g -1 The theoretical capacity combined with the advantages of a high potential platform of 4.7V (high energy density) is considered to be a highly promising cathode material for power lithium-ion batteries. However, the working potential close to 5V is undoubtedly a huge challenge for the existing electrolyte system. Commercial electrolytes will undergo oxidative decomposition at 4.2V and produce a large amount of by-products, which will endanger the safety performance and cycle life of the battery. At the same time, graphite, as one of the most mature negative electrode materials, has been widely used in lithium-ion batteries, but its performance at high rates is not satisfactory.

[0004] In response to these problems, people have taken many measures to improve them. For example, electroplating, coating and other methods are used to block the decomposition of the electrolyte, thereby inhibiting the polarization of the battery. Although surface modification can greatly improve the cycle performance of the battery, the process is relatively complicated and the positive electrode material needs to be processed in advance before assembling the battery, which brings inconvenience to commercial applications.

[0005] Based on this, an electrolyte and a preparation method thereof that can adapt to the operation of LNMO positive electrode materials of lithium-ion batteries at a high potential platform are provided, which inhibits the decomposition of the electrolyte by forming a controllable, highly stable, low-impedance interface film. This is of great significance for improving the safety performance and cycle life of lithium-ion batteries, and is also a technical problem that needs to be solved urgently. Summary of the invention

[0006] One of the objects of the present invention is to provide a lithium ion battery electrolyte which suppresses the decomposition of the electrolyte by forming a controllable, highly stable, low-impedance interface film.

[0007] A second object of the present invention is to provide a method for preparing a lithium-ion battery electrolyte by forming a controllable, highly stable, low-impedance interface film to inhibit the decomposition of the electrolyte.

[0008] A third object of the present invention is to provide a lithium ion battery with high safety performance and good cycle stability.

[0009] The technical solution adopted by the present invention to achieve one of the purposes is: to provide a lithium-ion battery electrolyte, including: an electrolyte lithium salt, an organic solvent and an additive; the additive is tri-thiophene boric acid, and its addition amount is 0.1wt.% to 10wt.% of the total mass of the electrolyte lithium salt and the organic solvent.

[0010] The invention mechanism and overall idea of ​​the present invention are as follows:

[0011] The lithium-ion battery electrolyte provided by the present invention adopts a new additive: tri-thiophene boric acid (3-TPBA), which is based on improving the interface performance between the electrolyte and the positive electrode material and the negative electrode material, bringing the following advantages:

[0012] First, 3-TPBA has excellent film-forming ability on the surface of the cathode material and can be oxidized before the electrolyte components. The dense interface film induced by it can effectively inhibit the continuous decomposition of the electrolyte and ensure the stability and integrity of the electrode structure.

[0013] Second, the CEI interface film containing boron (B) and sulfur (S) formed by 3-TPBA on the surface of the positive electrode material can significantly reduce the impedance of the lithium-ion battery, thereby improving the rate performance of the lithium-ion battery;

[0014] Third, 3-TPBA can be reduced in advance on the surface of the negative electrode material to form a SEI interface film, and effectively reduce the film impedance and interface impedance, thereby improving the cycle stability of the negative electrode material at a high rate;

[0015] Fourthly, the addition of 3-TPBA can form a highly stable and low-impedance interface film, which can inhibit the decomposition of the basic electrolyte and increase the conduction speed of lithium ions;

[0016] Fifth, due to the preferential redox film formation of 3-TPBA, ​​the interface performance of the positive and negative electrodes is improved, and it can adapt to a cut-off voltage of up to 4.9V, meeting the needs of high energy density lithium-ion batteries;

[0017] Sixth, 3-TPBA can be used directly as an additive, has a wide source, and is easy to obtain. It does not require secondary preparation processes such as substitution, coordination or polymerization, which can save a lot of costs.

[0018] In the present invention, controlling the addition amount of tri-thiophene boronic acid within a suitable range has an important influence on improving the cycle performance of lithium-ion batteries. Studies have shown that when the addition amount of 3-TPBA is too small, the improvement in the performance of lithium-ion batteries is not obvious; and when the addition amount of 3-TPBA is too much, the lithium-ion battery will experience overcharging in the first cycle, which will affect the application performance of the battery. Preferably, the addition amount of tri-thiophene boronic acid is controlled to be 0.5wt.% to 1.5wt.% of the total mass of the electrolyte lithium salt and the organic solvent. Under this condition, a controllable, highly stable, low-impedance interface film can be formed in situ to inhibit the decomposition of the electrolyte, and the use of additives can be reduced to save costs.

[0019] Furthermore, the purity of the tri-thiophene boronic acid is ≥98%.

[0020] Further, the electrolyte lithium salt includes one or more combinations of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate and lithium difluorooxalatoborate.

[0021] Furthermore, the concentration of the electrolyte lithium salt is 0.5-1.5 mol / L.

[0022] Further, the organic solvent is composed of a cyclic carbonate and a linear carbonate. Preferably, the mass ratio of the cyclic carbonate to the linear carbonate is 1:1 to 1:3. A large number of experiments have shown that within the range of this mass ratio, the prepared electrolyte can achieve a good balance between a high dielectric constant and a low viscosity, and has better electrochemical performance.

[0023] Among them, the cyclic carbonate includes: a combination of one or more of ethylene carbonate, propylene carbonate, butylene carbonate, butyrolactone, and valerolactone; the linear carbonate includes: a combination of one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, and propyl propionate.

[0024] Furthermore, the organic solvent accounts for 80% to 90% of the total mass of the electrolyte.

[0025] A second object of the present invention is to provide a method for preparing a lithium ion battery electrolyte, comprising the following steps:

[0026] S1, mixing cyclic carbonate and linear carbonate in a certain proportion, and obtaining an organic solvent after purification by removing impurities and water;

[0027] S2, adding electrolyte lithium salt to the organic solvent to obtain a raw electrolyte;

[0028] S3. Add trithiopheneboric acid in an amount equivalent to 0.1 wt.% to 10 wt.% of the mass of the raw electrolyte to the raw electrolyte to obtain a lithium ion battery electrolyte.

[0029] Preferably, the method for preparing the lithium ion battery electrolyte comprises the following steps:

[0030] S1, mixing a cyclic carbonate solvent and a linear carbonate solvent in a mass ratio of 1:1 to 1:3, and obtaining an organic solvent after purification by removing impurities and water;

[0031] S2. At room temperature, adding electrolyte lithium salt to the mixed organic solvent and standing to dissolve to obtain a raw electrolyte solution;

[0032] S3. Add trithiopheneboric acid equivalent to 0.5wt.% to 1.5wt.% of the mass of the raw electrolyte to the raw electrolyte and let it stand to dissolve, so as to obtain a lithium ion battery electrolyte.

[0033] The third object of the present invention is to provide a lithium-ion battery, comprising: a positive electrode sheet containing a positive electrode active material, a negative electrode sheet containing a negative electrode active material, a separator, and the lithium-ion battery electrolyte according to one of the objects of the present invention.

[0034] Furthermore, the positive electrode active material includes one or more combinations of lithium-containing oxides. For example: Li 1- x MnO2、Li 1-x Mn2O4、Li 1-x CoO2、Li 1-x NiO2, LiV2O3 and their derivatives, stable free radical compounds. It should be noted that x in these positive electrode active materials represents a number of 0 to 1. The negative electrode active material includes a combination of one or more of carbon materials, silicon-based materials, and lithium metal. The electrolyte provided by the present invention is based on the mechanism of improving interface performance, and can have a certain improvement effect on the cycle performance of the above-mentioned positive electrode materials and negative electrode materials.

[0035] Preferably, the positive electrode active material is LiNi 0.5 Mn 1.5O4 (LNMO); the negative electrode active material is graphite. It has been found that the electrolyte containing 3-TPBA provided by the present invention has the best performance in the lithium ion battery with LNMO positive electrode and graphite negative electrode: after adding the additive 3-TPBA in the same mass ratio, both the LNMO positive electrode and the graphite negative electrode can show the best electrochemical performance. In addition, the electrolyte provided by the present invention can also well adapt to the cut-off voltage of 4.9V of the LNMO positive electrode, meeting the needs of high energy density lithium ion batteries.

[0036] Furthermore, the diaphragm is selected from a polyethylene diaphragm and / or a polypropylene diaphragm.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention provides a lithium-ion battery electrolyte and a preparation method thereof. The electrolyte uses tri-thiophene boric acid 3-TPBA as an additive. Since 3-TPBA has a low oxidation potential, it can form an effective CEI film before the positive electrode material of the lithium-ion battery deintercalates lithium ions, thereby inhibiting the decomposition of the electrolyte in subsequent reactions. In addition, 3-TPBA also has the ability of preferential reduction, and can form a low-impedance SEI film on the surface of the negative electrode material, thereby improving the battery's cycle performance at a high rate.

[0039] (2) The present invention provides a lithium-ion battery electrolyte, which contains a bifunctional additive tri-thiophene boric acid (3-TPBA) that can improve 5V-level LNMO positive electrode materials and graphite negative electrode materials. On the one hand, 3-TPBA has excellent film-forming ability on the surface of LNMO positive electrode materials, and can be oxidized before the electrolyte components. The interface induced by it can effectively inhibit the continuous decomposition of the electrolyte and ensure the stability and integrity of the electrode structure; on the other hand, 3-TPBA can also be reduced in advance on the graphite negative electrode to form an SEI interface film, and effectively reduce the membrane impedance and interface impedance, and improve the cycle stability of the graphite negative electrode at a high rate. The electrolyte prepared by the present invention can adapt to the high potential platform of the LNMO positive electrode material of the lithium-ion battery, inhibit the decomposition of the electrolyte by forming a controllable, highly stable, low-impedance interface film, significantly improve the safety performance and cycle life of the lithium-ion battery, and has broad promotion and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The electrolytes prepared in Example 2 and Comparative Example 1 are respectively applied to lithium nickel manganese oxide half-cells for cycle testing comparison;

[0041] Figure 2 A comparison diagram of HOMO and LUMO energy levels obtained by DFT theoretical calculation of the main solvent components in the electrolytes prepared in Example 2 and Comparative Example 1;

[0042] Figure 3 The results of the linear potential scanning test of the electrolytes prepared in Example 2 and Comparative Example 1 respectively applied to Li / Pt batteries are compared;

[0043] Figure 4 AFM images of the electrolytes prepared in Example 2 and Comparative Example 1 respectively applied to lithium nickel manganese oxide half-cells after 200 cycles;

[0044] Figure 5 TEM and SEM images of the electrolytes prepared in Example 2 and Comparative Example 1 respectively applied to lithium nickel manganese oxide half-cells cycled 200 times;

[0045] Figure 6 A comparison chart of the cycle tests of the electrolytes prepared in Example 2 and Comparative Example 1 respectively applied to graphite half-cells;

[0046] Figure 7 A comparison chart of the results of cyclic voltammetry tests of the electrolytes prepared in Example 2 and Comparative Example 1 respectively applied to graphite half-cells;

[0047] Figure 8 A comparison chart of impedance test results after the electrolytes prepared in Example 2 and Comparative Example 1 were respectively applied to graphite half-cells for 200 cycles;

[0048] Fig. 9 A comparison chart of impedance test results after the electrolytes prepared in Example 2 and Comparative Example 1 were respectively applied to a lithium nickel manganese oxide half-cell and cycled for 200 cycles;

[0049] Fig.10 The electrolytes prepared in Example 2 and Comparative Example 1 are respectively applied to the rate performance comparison chart of the lithium nickel manganese oxide half-cell at 0.2C, 0.5C, 1.0C, 3.0C, 5.0C, 7.0C, 10.0C and after returning to 0.2C. DETAILED DESCRIPTION

[0050] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0052] The present invention provides a lithium ion battery electrolyte, comprising: an electrolyte lithium salt, an organic solvent and an additive; wherein the additive is tri-thiophene boronic acid which can form an excellent interface film on the surface of the positive electrode and the negative electrode through oxidation and reduction. The addition amount of tri-thiophene boronic acid is 0.1wt.% to 10wt.%, preferably 0.5wt.% to 1.5wt.% of the total mass of the electrolyte lithium salt and the organic solvent.

[0053] It should be noted that tri-thiophene boronic acid, English name: 3-Thienylboronic acid, CAS number: 6165-69-1, molecular formula: C4H5BO2S, molecular weight: 127.9600, also known as 3-TPBA. The tri-thiophene boronic acid used in the present invention is a commercially available raw material with a purity of ≥98%.

[0054] In the above-mentioned lithium ion battery electrolyte, the electrolyte lithium salt includes one or more combinations of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate and lithium difluorooxalatoborate, and the concentration of the electrolyte lithium salt is 0.5 to 1.5 mol / L.

[0055] The organic solvent is a mixture of cyclic carbonate and linear carbonate in a mass ratio of 1:1 to 1:3. The cyclic carbonate includes one or more of ethylene carbonate, propylene carbonate, butylene carbonate, butyrolactone, and valerolactone; the linear carbonate includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, and propyl propionate. The organic solvent accounts for 80% to 90% of the total mass of the electrolyte.

[0056] The present invention provides a method for preparing a lithium ion battery electrolyte, comprising the following steps:

[0057] Step 1: mixing a cyclic carbonate solvent and a linear carbonate solvent in a mass ratio of 1:1 to 1:3, and obtaining an organic solvent after purification by removing impurities and water;

[0058] Step 2: Under room temperature, adding electrolyte lithium salt to the mixed organic solvent and standing to dissolve to obtain a raw electrolyte solution;

[0059] Step 3: Add tri-thiophene boric acid equivalent to 0.1wt.% to 10wt.% of the mass of the raw electrolyte to the raw electrolyte and let it stand to dissolve to obtain a lithium-ion battery electrolyte.

[0060] The present invention also provides a lithium-ion battery, comprising: a positive electrode sheet containing a positive electrode active material, a negative electrode sheet containing a negative electrode active material, a separator and the above-mentioned lithium-ion battery electrolyte. Specifically, the following materials may be included:

[0061] (1) Positive electrode material:

[0062] As the positive electrode active material, it can include various lithium-containing oxides, such as: Li 1-x MnO2、Li 1-x Mn2O4、Li 1- x CoO2、Li 1-x NiO2, LiV2O3 and their derivatives, stable free radical compounds. It should be noted that x in these positive electrode active materials represents a number from 0 to 1. As the conductive material of the positive electrode, graphite particles, acetylene black, Ketjen black, carbon black such as carbon nanofibers, amorphous carbon particles such as needle coke, etc. can be used, but are not limited thereto.

[0063] In an optional embodiment, the positive electrode active material is LNMO. By comparing positive electrode active materials such as NCM811, NCM622, LCO, and LNMO, a large number of experiments have shown that after adding additives of the same mass ratio, LNMO positive electrode active material exhibits the best electrochemical performance.

[0064] (2) Negative electrode material:

[0065] As the negative electrode active material, it can include various carbon-containing compounds, such as hard carbon, acetylene black, graphite and their derivatives, stable compounds, various silicon-based materials, such as crystalline silicon, nano silicon, silicon oxide and other silicon mixtures, and lithium metal can also be used as the negative electrode.

[0066] In an optional embodiment, the negative electrode active material is graphite.

[0067] (3) Material of the diaphragm: selected from polyethylene diaphragm or polypropylene diaphragm.

[0068] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0069] Example 1

[0070] This embodiment provides a lithium ion electrolyte, and the preparation method thereof is as follows:

[0071] (1) mixing cyclic carbonate solvent ethylene carbonate (EC) and linear carbonate solvent ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of EC:EMC:DEC=3:5:2, and purifying and removing impurities and water (water content <10 ppm) by using molecular sieves, calcium hydride, and lithium hydride;

[0072] (2) at room temperature, dissolving the conductive lithium salt LiPF6 in the solvent obtained in step (1), with the final concentration of the conductive lithium salt being 1.0 mol / L, stirring evenly, and standing to obtain a common electrolyte;

[0073] (3) Add trithiopheneboric acid to the common electrolyte prepared in step (2) in an amount of 0.5 wt.% of the common electrolyte to obtain a final electrolyte.

[0074] Example 2

[0075] This embodiment provides a lithium ion electrolyte, and the preparation method thereof is as follows:

[0076] (1) mixing cyclic carbonate solvent ethylene carbonate (EC) and linear carbonate solvent ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of EC:EMC:DEC=3:5:2, and purifying and removing impurities and water (water content <10 ppm) by using molecular sieves, calcium hydride, and lithium hydride;

[0077] (2) at room temperature, dissolving the conductive lithium salt LiPF6 in the solvent obtained in step (1), with the final concentration of the conductive lithium salt being 1.0 mol / L, stirring evenly, and standing to obtain a common electrolyte;

[0078] (3) Add trithiopheneboric acid to the common electrolyte prepared in step (2) in an amount of 1.0 wt.% of the common electrolyte to obtain a final electrolyte.

[0079] Example 3

[0080] This embodiment provides a lithium ion electrolyte, and the preparation method thereof is as follows:

[0081] (1) mixing cyclic carbonate solvent ethylene carbonate (EC) and linear carbonate solvent ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of EC:EMC:DEC=3:5:2, and purifying and removing impurities and water (water content <10 ppm) by using molecular sieves, calcium hydride, and lithium hydride;

[0082] (2) At room temperature, dissolve the conductive lithium salt LiPF6 in the solvent obtained in step (1), with the final concentration of the conductive lithium salt being 1.0 mol / L. Stir evenly and allow to stand to obtain a common electrolyte.

[0083] (3) Add trithiopheneboric acid to the common electrolyte prepared in step (2) in an amount of 1.5 wt.% of the common electrolyte to obtain a final electrolyte.

[0084] Example 4

[0085] This embodiment provides a lithium ion electrolyte, and the preparation method thereof is as follows:

[0086] (1) mixing cyclic carbonate solvent ethylene carbonate (EC) and linear carbonate solvent ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of EC:EMC:DEC=3:5:2, and purifying and removing impurities and water (water content <10 ppm) by using molecular sieves, calcium hydride, and lithium hydride;

[0087] (2) At room temperature, dissolve the conductive lithium salt LiPF6 in the solvent obtained in step (1), with the final concentration of the conductive lithium salt being 1.0 mol / L. Stir evenly and allow to stand to obtain a common electrolyte.

[0088] (3) Add trithiopheneboric acid to the common electrolyte prepared in step (2) in an amount of 0.1 wt.% of the common electrolyte to obtain a final electrolyte.

[0089] Example 5

[0090] This embodiment provides a lithium ion electrolyte, and the preparation method thereof is as follows:

[0091] (1) mixing cyclic carbonate solvent ethylene carbonate (EC) and linear carbonate solvent ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of EC:EMC:DEC=3:5:2, and purifying and removing impurities and water (water content <10 ppm) by using molecular sieves, calcium hydride, and lithium hydride;

[0092] (2) At room temperature, dissolve the conductive lithium salt LiPF6 in the solvent obtained in step (1), with the final concentration of the conductive lithium salt being 1.0 mol / L. Stir evenly and allow to stand to obtain a common electrolyte.

[0093] (3) Add trithiopheneboric acid to the common electrolyte prepared in step (2) in an amount of 10 wt.% of the common electrolyte to obtain a final electrolyte.

[0094] Comparative Example 1

[0095] The common electrolyte obtained in step (2) of Example 2 was used as a control.

[0096] Application Examples

[0097] Preparation of positive electrode: LiNi 0.5 Mn 1.5O4 (LNMO), polytetrafluoroethylene adhesive (PVDF) and conductive agent acetylene black are dissolved in an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 8:1:1. The slurry is evenly coated on the current collector aluminum foil, first dried in an oven at 80°C for 1h, and then transferred to 120°C for vacuum drying for 12h, and cut into electrodes with a diameter of 12mm for use.

[0098] Preparation of negative electrode sheets: Graphite, polytetrafluoroethylene binder (PVDF) and conductive agent acetylene black are dissolved in an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 8:1:1, and the slurry is evenly applied on the current collector aluminum foil, first dried in an oven at 80°C for 1h, and then transferred to 120°C for vacuum drying for 12h, and cut into electrodes with a diameter of 12mm for use.

[0099] The prepared positive electrode sheet and negative electrode sheet were assembled with the electrolytes of Examples 1-5 and Comparative Example 1, respectively (the separator model used was Celgard 2400) to obtain Li / LNMO half-cells, which were subjected to cycle tests. The test results are shown in Table 1 below.

[0100] Table 1

[0101]

[0102] As can be seen from the above table,

[0103] The capacity of the Li / LNMO half-cell made of the electrolyte with 3-TPBA added in Example 1-5 after 200 cycles at 4.9V at 1C rate is 67.5-121.1 mAh / g, and the capacity retention rate is 52.1%-93.7%, which is significantly better than the capacity retention rate of the LNMO half-cell with ordinary electrolyte in Comparative Example 1 under the same test conditions. Compared with Examples 4 and 5, Example 1-3 controls the addition amount of 3-TPBA to 0.5%-1.5% of the total weight of the electrolyte, and the half-cell cycle performance is better. The capacity after 200 cycles at 4.9V at 1C rate is 111.8-121.1 mAh / g, and the capacity retention rate is 86.5%-93.7%.

[0104] In addition, according to Figure 1 The comparison results also show that the LNMO half-cell cycled in the ordinary electrolyte of Comparative Example 1 shows obvious capacity decay, and the capacity retention rate after 200 cycles is only 34.7% of the initial capacity. In Example 2, the electrolyte containing additives has a capacity retention rate of 93.7% after 200 cycles, which shows that controlling 3-TPBA in the electrolyte within a suitable range can significantly improve the cycle stability of the LNMO / Li half-cell.

[0105] Figure 2 , Figure 3 The HOMO and LUMO values ​​obtained by theoretical calculation and the LSV test results of the LNMO / Li half-cell in the electrolyte of Comparative Example 1 and the electrolyte of Example 2. From the HOMO and LUMO calculation results, it can be seen that the highest occupied orbital (HOMO) energy of 3-TPBA is -6.74eV, which is significantly higher than the HOMO energy of DEC, EMC, and EC, indicating that the molecule has a greater ability to lose electrons and its oxidation activity is the highest. At the same time, the LUMO energy of 3-TPBA is -0.99eV, which is much lower than the LUMO energy of DEC, EMC, and EC, indicating that the molecule gains electrons. The same result can be confirmed in the LSV comparison diagram, and the LNMO half-cell has an oxidation current in advance during the linear potential scan in Example 2.

[0106] Figure 4 , Figure 5 The AFM, SEM and TEM test comparison chart of the LNMO positive electrode material after the LNMO / Li half-cell is cycled in Comparative Example 1 and Example 2. After 200 cycles, the median Young's modulus of the LNMO pole piece in the ordinary electrolyte of Comparative Example 1 after the cycle is about 8.5, which is lower than the Young's modulus of the interface film of the pole piece after the cycle in Example 2, indicating that the interface film formed by the decomposition of Comparative Example 1 has a smaller hardness and lower stability. The test results of TEM and SEM show that the interface film formed by the decomposition of the basic electrolyte is harder than the surface covered with a large amount of decomposition products, generating an uneven interface film. The thickness of the film varies greatly, with the thickest part being about 81nm of accumulated decomposition products, while the thinnest part is where the material body is exposed. In contrast, the interface film formed on the surface of the LNMO pole piece after the cycle in the electrolyte of Example 2 is very uniform, with a thickness of about 9nm. At the same time, the surface of the LNMO pole piece cycled in Example 2 is very smooth, and there is no large amount of decomposition product deposition.

[0107] Figure 6 , Figure 7 The CV test diagram of Li / Graphite shows that the electrolyte of Example 2 can also be preferentially reduced. Figure 2 The results of the cycling test showed that after the graphite half-cell cycled 200 times at a rate of 0.5C, the capacity retention rate of the battery increased from 45.3% to 70.1%. Figure 8 The EIS test results of the Li / Graphite half-cell after long cycling show that the interfacial film formed by 3-TPBA can significantly inhibit the increase of battery impedance after long cycling, thereby improving the battery capacity retention rate.

[0108] Fig. 9The EIS test results of the Li / LNMO half-cell after long-term cycling show that the interfacial film formed by the premature oxidation of 3-TPBA can effectively inhibit the decomposition of the electrolyte and reduce the impedance of the battery after long-term cycling, thereby improving the capacity retention rate of the battery, thanks to the inhibitory effect of 3-TPBA on impedance.

[0109] from Fig.10 From the comparison of rate performance (cut-off voltage is 4.9V), we can see that the addition of 3-TPBA can improve the capacity of the battery at high rates, especially at 7.0C and 10.0C. Data comparison shows that the capacity of the battery containing 3-TPBA at 10.0C is as high as 92.5%. In contrast, the capacity of the LNMO / Li half-cell in the basic electrolyte at 10.0C is only 80.2%.

[0110] In summary, the present invention relates to a lithium-ion battery electrolyte, a preparation method and a lithium-ion battery. The lithium-ion battery electrolyte comprises: an electrolyte lithium salt, an organic solvent and an additive; the additive is tri-thiophene boric acid. The additive can be oxidized on the surface of the positive electrode to form a stable interface film. The film formed by the additive can effectively inhibit the decomposition of the electrolyte and reduce the impedance of the interface. On the other hand, the additive can effectively protect the positive electrode material body, and lithium nickel manganese oxide can still maintain the same lattice as the fresh electrode after a long cycle in a solution containing the additive, thereby effectively curbing the attenuation of capacity.

[0111] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.

Claims

1. An application of a lithium ion battery at a cut-off voltage of 4.9V, characterized in that: The lithium-ion battery comprises: Positive electrode sheet, the positive electrode sheet contains positive electrode active material LiNi 0.5 Mn 1.5 O4; A negative electrode sheet, wherein the negative electrode sheet comprises graphite, a negative electrode active material; A separator; and a lithium-ion battery electrolyte, wherein the electrolyte comprises an electrolyte lithium salt, an organic solvent and an additive, wherein the additive is tri-thiophene boric acid, and the additive amount thereof is 1.0 wt.%-1.5 wt.% of the total mass of the electrolyte lithium salt and the organic solvent; When the lithium-ion battery is charged to a cut-off voltage of 4.9V, the capacity retention rate after 200 cycles at a rate of 1C is 92.5%-93.7%.

2. The use according to claim 1, characterized in that: The electrolyte lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate and a combination of lithium difluorooxalatoborate.

3. The use according to claim 1, characterized in that: The concentration of the electrolyte lithium salt is 0.5-1.5 mol / L.

4. The use according to claim 1, characterized in that: The organic solvent is prepared by mixing cyclic carbonate and linear carbonate in a mass ratio of 1:1-1:

3.

5. The use according to claim 1, characterized in that: The preparation method of the lithium ion battery electrolyte comprises the following steps: S1, mixing cyclic carbonate and linear carbonate in a certain proportion, and obtaining an organic solvent after purification by removing impurities and water; S2, adding electrolyte lithium salt to the organic solvent to obtain a raw electrolyte; S3. Add trithiopheneboric acid equivalent to 1 wt.%-1.5 wt.% of the mass of the raw electrolyte to the raw electrolyte to obtain a lithium ion battery electrolyte.

6. The use according to claim 1, characterized in that: The diaphragm is selected from a polyethylene diaphragm and / or a polypropylene diaphragm.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte capable of improving positive and negative electrode film formation

    CN111313092A

  • Nonaqueous electrolyte and nonaqueous electrolyte secondary battery containing nonaqueous electrolyte

    JP2009245829A